ANALISIS PEMAHAMAN SISWA SEKOLAH DASAR TERHADAP KONSEP RUANG DAN WAKTU DALAM SEJARAH: ANALISIS PEMAHAMAN SISWA SEKOLAH DASAR TERHADAP KONSEP RUANG DAN WAKTU DALAM SEJARAH - Emanuel Hosa Kurnia Adi; Femi Br Ginting; Marsya; Silvina Noviyanti (Jurnal Tunas Pendidikan, 2024)
History education in elementary schools plays a critical role in shaping students' understanding of the concepts of space and time. This research aims to analyze the extent of students' understanding of this concept. A good understanding of temporal and spatial dimensions not only creates the basis for in-depth historical knowledge, but also strengthens the links between historical events, geographic locations, and the development of civilization. Factors such as teachers' teaching methods, textbooks, and students' personal experiences influence their understanding. Interactive teaching methods and textbooks that support learning activities make a positive contribution, while the complexity of textbooks can be an obstacle. Personal experiences, such as visits to historical sites, also influence students' understanding. The research results contribute to the development of history curricula by emphasizing a variety of teaching methods, textbook selection, and the integration of students' personal experiences. The research implications can improve teaching methods and learning materials, utilizing interactive approaches and diverse resources. This research plays a role in developing more effective history learning strategies by understanding the factors that shape student understanding. Overall, the research results provide insight into improving the effectiveness of history learning at the elementary school level through a better understanding of the concepts of space and time.